2014
DOI: 10.5551/jat.23663
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Mediates Indoxyl Sulfate-Induced Cellular Senescence in Human Umbilical Vein Endothelial Cells

Abstract: Aim: Vascular senescence, which is accelerated in individuals with chronic kidney disease (CKD), contributes to the development of cardio-renal syndrome, and various uremic toxins may play important roles in the mechanisms underlying this phenomenon. We recently reported that indoxyl sulfate (IS), a uremic toxin, directly activates aryl hydrocarbon receptor (AhR) and generates oxidative stress through NADPH oxidase-4 in human umbilical vein endothelial cells (HUVECs). In the current study, we sought to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…18, 19 In the present study, we evaluated the NAD + /NADH ratio and Sirt1 activity accordance with a previous report. 24 As shown in Figure 8, chrysin treatment abolished the antioxidative and anti-senescence effects of hydrogen on HUVECs at 24 h after TCDD exposure.…”
Section: Effects Of Hydrogen-rich Medium On Nad + /Nadh Ratio and Sirmentioning
confidence: 59%
See 3 more Smart Citations
“…18, 19 In the present study, we evaluated the NAD + /NADH ratio and Sirt1 activity accordance with a previous report. 24 As shown in Figure 8, chrysin treatment abolished the antioxidative and anti-senescence effects of hydrogen on HUVECs at 24 h after TCDD exposure.…”
Section: Effects Of Hydrogen-rich Medium On Nad + /Nadh Ratio and Sirmentioning
confidence: 59%
“…A chrysin concentration of 10 μmol/L was selected, in IS reduced cellular NAD + and suppressed Sirt1 activity, thereby accelerating cellular senescence. 18, 19 When we first examined whether H2 suppresses oxidative stress by means of the TCDD-AhR pathway, we found that in hydrogen-rich medium, the TCDD-induced increase in 8OHdG in HUVECs was significantly suppressed and that these effects were similar to those of the AhR-inhibitor, CH. We then sought to determine whether the antioxidative effects of H2 in HUVECs depended on inhibition of AhR.…”
Section: Effects Of Chrysin On H2-induced Changes In Huvecsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Barreto et al showed that serum indoxyl sulfate progressively increases with stages of chronic kidney disease and is associated with the incidence of cardiovascular disease and overall mortality in patients with chronic kidney disease 12) . Several studies have suggested that indoxyl sulfate aggravates cardiovascular disease by inducing cardiac cell fibrosis, endothelial senescence, proliferation of vascular smooth muscle cells, and activation of monocytes/ macrophages via an oxidative stress-dependent pathway [14][15][16][17][18][19][20][21][22] . In addition, we previously showed that indoxyl sulfate enhances cytokine-induced leukocyteendothelial interactions through E-selectin in vivo and in vitro, and this process is mediated by activation of oxidative stress-dependent intracellular signaling such as JNK and NF-B in human umbilical vein endothelial cells (HUVEC) 23) .…”
Section: Laboratory Animalsmentioning
confidence: 99%